PENGEMBANGKAN USAHA HOME INDUSTRI DI KENAGARIAN ANDALEH KECAMATAN BATIPUH KABUPATEN TANAH DATAR - Merry Thressia; Irnawati Siregar; Mulyadi Mulyadi (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Home industry is a perpetrator of economic activities carried out at home, family, or one of the family members who live in their homes by inviting several people who are nearby as employees. One area that has a home industry is in Kenagarian Andaleh, Batipuh Subdistrict, Tanah Datar District, West Sumatra Province. Home industry is managed in the form of a traditional food named Aluo Cake and Randang Karambia which is produced by the local community. Both of these cakes in terms of taste are very tasty and unique. After conducting a field survey several problems were found, namely the limited ability of human resources in processing the results of existing businesses and home industries not ready to make business plans in accordance with market needs. The purpose of this community service activity is to provide understanding and knowledge to home industry players to increase community income through KSM (self-help groups) in terms of processing business results and making business plans in accordance with market needs, so that in the future it is hoped that this home industry will be able and can develop business results both nationally and internationally. This activity lasted for 3 (three) days with lecture method, brainstorming, discussion and direct practice to the field with 15 (fifteen) participants of home industry. The results of this activity are 1). Participants can understand the basic concepts of entrepreneurship about the importance of making business plans and developing business results to last long in the market, 2). Participants are able to change the form of packaging to be more attractive at competitive prices on the market, 3). actively following IT developments so they can market their products to a wider area with maximum results.